Pengaruh Service Quality Terhadap Customer Loyalty Dengan Customer Satisfaction Sebagai Variabel Intervening Di Front One Inn De Laia Malang - Nur Rohmah Dhuhaini; Muhammad Ridwan Basalamah; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The intense competition for hotels in Malang City makes hotel managers try to improve the quality of their services so that customers feel satisfied and customer loyalty can be created. Therefore, understanding and studying the effect of service quality on customer loyalty by mediating customer satisfaction at Front One Inn De Laia Malang becomes the purpose of conducting this research. This type of research is Explanatory research with a quantitative approach. The data source is primary, by distributing questionnaires to 83 respondents through likert scale assessment. Simple Random Sampling is the sampling technique in this study. The data analysis method applied through the SPSS version 25 program was Instrument Test (Validity Test, Reliability Test), Normality Test, Path Analysis, Sobel and Hypothesis Test (Partial Test {t Test}. Obtained research data stated that service quality directly had a positive and significant effect on customer satisfaction at Front One Inn De Laia Malang, service quality had a positive and significant effect on customer loyalty at Front One Inn De Laia Malang, customer satisfaction had a positive and significant effect on customer loyalty at Front One Inn De Laia Malang. Meanwhile, the acquisition from the test indirectly prove that costumer satisfaction has an effect as a mediating relationship between service quality to costumer loyalty at Front One Inn De Laia Malang. Keywords: Service Quality, Customer Loyalty, Customer Satisfaction